Evaluación de algunas características físicas de un suelo dedicado a la siembra directa y convencional de maíz en la zona de Babahoyo, Los Ríos - Muñoz Lozada, Marcos Gabriel (2016)
SUMMARY The work was carried out in the lands of the experimental farm "San Pablo", located in Km. 7.5 of the road Babahoyo-Montalvo. Two siembra systems and 3 sampling depths were investigated with 4 repetitions in parcels of 20 m2. The objective of this investigation it was to determine the main ones characteristic and physical properties of a floor, in a system of direct and conventional crop; also to evaluate the development and yield of the cultivation of low corn the conditions of direct crop. 6 treatments were investigated with four repetitions and they were distributed at random in a design of blocks in divided parcels. For the evaluation of stockings the test was used from Tukey to 5 significancia%. At the end of the cycle of the cultivation plant height, height of ear insert, ear diameter was evaluated, ear longitude, days to flowering, days to crop, weight 100 grains and yield for hectare. The variables of floors floor fueron:profundidad, color, grain, structures, density, porosity, retention of humidity, infiltration, analysis of chemical and potential hydrogen. The results determined that the properties of the floor have influence on the agronomic factors and of yield of the cultivation of corn. They didn't impact on plant height, days to the floración, ear longitude and weight of 100 grains. The system of conventional crop with sampling to 20 cm of depth achieved 6762,0 kg/ha, superior yield to other treatments.